(untitled) (Research, Society and Development, 2021)
The study aims to use the literature as a reference to discuss important aspects on the topic of premenstrual tension, in a comprehensive and organized way, with a nutritional focus. This is an integrative review, in which the search was performed in the following databases: Pubmed, LILACS and SciELO, using the following descriptors available in the Health Sciences Descriptors (DeCS): Premenstrual syndrome, Nutritional therapy and behavior to feed. The Boolean operators “AND” and “OR” were used, performing different combinations. During a woman’s reproductive period, many of the problems that affect her health are associated with hormonal fluctuations related to the menstrual period. During this phase, some women may have different symptoms, such as: depression, anxiety, cramps, irritability, fatigue, behavioral change, headache, muscle pain and water retention. In this sense, it is necessary to verify the influence of food on women’s health during this period and how these changes affect their routine. Changes in eating behavior are common on PMS days, as interest in ultra-processed foods, which are rich in sugars and fats, is intensified, which can have negative consequences for women’s health. Thus, it is necessary that women seek to maintain a good diet and control stress. A diet consisting of vegetables, lean protein sources, whole grains, and low-fat foods can all contribute to symptom relief. Therefore, it is legitimate that a balanced diet in macro and micronutrients positively affects the health of women during their menstrual cycle.